Spilling Over and Crowding Out: The Effects of Public Sector/Private Sector Convergence and Competition, in the Provision of Public Goods - Diana Barrowclough (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper develops an original model of product differentiation, to contribute to the debate about theregulation and finance of public television. It goes beyond the conventional analysis in this topic, byshowing the spill-over effects that a public broadcaster can have upon commercial broadcasters. It showshow the existence of a publicly-financed, free-to-air channel (such as the BBC) can affect the behaviour ofadvertiser-financed, free-to-air channels (such as the ITV). In particular, it shows what happens if theoutput of the public channel converges with that offered by private firms, so that it becomes lessdistinctive; and or it introduces advertising.These are timely issues, given the extent to which public broadcasters are increasingly criticised forseeking popularity, losing distinctiveness, and in many cases, introducing advertising. These tensions arebeing felt in the television sectors of virtually every country of the world. To illustrate these and otherquestions of this nature, we develop a model that clarifies the interplay of the key issues. Moreover, themodel has wider parallels to other sectors where services are also offered free at the point of access, butfinanced by advertising. The most obvious example is the internet.The following pages therefore develop an original model of product differentiation in two dimensions,following the tradition of Hotelling and Cournot competition. The horizontal product attribute is programmequality or type, and the vertical attribute is level of advertising. Broadcasters compete for viewers byaltering their levels of advertising. The second novelty of this model is its pricing scheme, which capturesthe unusual nature of television advertising markets. Channels sell quantities of airtime to advertisers, theunit price of which is determined by the number of viewers. Relative demand therefore plays the role ofprice in a Cournot model, except there can be different prices for diff
Keywords: 330; spatial competition; product differentiation; television; advertising.